Growth, Income Distribution, and Well-Being in Transition Countries - Carola Grün; Stephan Klasen (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2000)
In this paper we use several well-being measures that combine average income with a measure of inequality to undertake international and intertemporal well-being comparisons in transition countries. Our well-being measures drastically change the impression of levels and changes in well-being from a traditional reliance on income measures. They also significantly affect the ranking of countries, when compared to rankings based on real incomes. Due to low inequality and moderate income levels, socialist countries enjoyed relatively high levels of economic well-being. In the transition process, rising inequality and falling incomes have led to a dramatic decline in well-being in many transition countries, and a corresponding worsening in rank when compared to other countries. There is great variance in the income and inequality performance of transition countries. We find a close correlation between income losses and inequality increases suggesting the ability of appropriate policies to reduce the income losses and reduce rising inequality. While the political dimension of transformation remains largely successful, our indicators suggest that most transition countries have yet to reach the level of economic well-being enjoyed in the late 1980s.
urn:nbn:de:bvb:19-epub-26-0
Keywords: 330